Feeding Jejunostomy in Pancreatico-Duodenectomy patients: Is it important - Ahmed Mohamed Abdelaziz Hassan; Hesham A. Elmeligy; Magdy Elsebae; Mohamed Abdo; Ahmed M. Azzam; Mahmoud Rady (Clinical Surgical Oncology)
Background: During a pancreaticoduodenectomy, Feeding Jejunostomy (FJ) is frequently placed to improve postoperative nutrition. Our aim is to ascertain the effects of the FJ tube after pancreaticoduodenectomy. Methods: Prospective analysis was performed on all patients who underwent concurrent FJ after pancreaticoduodenectomy (Whipples surgery) between 2022 and 2023. On POD 1, FJ feeds were frequently initiated. After the patient had taken enough oral feeds, the jejunostomy feeds were stopped. Frequency and mean were used to represent the data. Results: A total of 48 patients underwent pancreaticoduodenectomy with concomitant FJ. A total of 35 (72.9%) were men and the mean age was 49.2 years. The majority (28, 58.3 %) of these patients had cancer head of the pancreas as an indication for surgery. Only 13 out of 48 (27%) patients required nutrition supplementation through FJ on POD 10. Only 1 out of 48 (2%) patients required FJ feeds on POD 30. None of these patients had tube-related complications in the 30-day postoperative period. There was a single FJ-related mortality in the 30-day postoperative period due to pulmonary embolism. The patients, who required prolonged FJ feeds had grade C pancreatic leaks, delayed gastric emptying, and surgical site infection. Conclusion: The routine use of concurrent FJ in patients undergoing pancreaticoduodenectomy has a good outcome, especially for those who require prolonged postoperative nutritional supplementation because of grade c pancreatic leak and delayed gastric emptying.